Hematological impact of COVID-19 mRNA vaccination in patients treated with Clozapine - A. Touiti; I. Yaich; C. Ben Said; N. Bram (European Psychiatry, 2024)
Introduction Clozapine is an atypical antipsychotic that is primarily prescribed for treatment-resistant schizophrenia. Despite its proven efficacy, the prescription of clozapine is sometimes limited by its hematologic side effects, including agranulocytosis. During the SARS-CoV-2 pandemic, schizophrenia is recognized as a risk factor for developing severe forms of the infection. Early and complete vaccination of patients has been recommended. However, there is limited data on the effect of the vaccine on the risk of hematologic abnormalities in patients treated with clozapine.